Incidence and clinical profile of rotaviral infection among children below 5 years of age admitted with acute diarrhea in a tertiary care hospital of Tripura - Barbhuiya, Nazrul Islam; Majumder, Nilratan; Majumder, Tapan; Chakraborty, Jayanti (Indian Journal of Child Health, 2017)
Background: Acute diarrheal disease is a major cause of childhood morbidity and mortality. Rotavirus has been recognized as the most common cause of severe diarrhea in children. Data on rotaviral disease burden are needed across India to support reasonable, evidence-based decision regarding any intervention. Objectives: The objectives of the study were to study the incidence of rotavirus infection in acute diarrhea among children below 5 years and clinical profile of rotaviral diarrhea. Materials and Methods: This cross-sectional study was conducted in a teaching institution of Tripura from November 1, 2014, to April 30, 2016. Stool samplesfrom 460 hospitalized children below 5 years admitted with acute diarrhea were tested for rotaviral antigen by ELISA method. Caregivers were interviewed, physical examination was conducted, assessment of dehydration was done, and cases were managed as per the WHO Guideline. Results: Out of 460 cases of acute diarrhea, 290 (63%) were male and 170 (37%) were female. In infants, 240 (52%) diarrheal cases were observed. Out of total 460 stool samples, 166 (36%) were rotavirus positive, and of these, 100 (60.24%) rotavirus positive cases were infant, and 102 (61.44%) were male children. Rotavirus infection was observed throughout the year, with peak (54.21%) during January–March (winter season). Clinically, 110 (66.26%) children had fever, 94% (156) cases had vomiting, and 63.25% (105) children of rotaviral diarrheal cases were admitted with some dehydration, and 33.13% (55) patients were admitted with severe dehydration. The mean duration of diarrhea (4.97 days) and mean duration of hospital stay (3.71 days) were significantly higher in rotaviral diarrhea as compared with non-rotaviral diarrhea. No death was observed. Out of 460 cases of acute diarrhea, only 6 (1.3%) cases had received rotaviral vaccine, and only one case (0.6%) among 166 rotaviral diarrhea cases had received rotaviral vaccine. Conclusion: This study highlights that rotavirus is a significant cause of acute diarrhea in this part of the country and mainly affects children below 12 months age.